Penetapan Harga Jual Beli Ikan Oleh Toke Bangku Di Tpi Lampulo, Aceh, Indonesia Ditinjau dari Perspektif Adat dan Ekonomi Islam - Ida Yanti (Ar-Raniry: International Journal of Islamic Studies, 2020)
TPI Lampulo is one of the biggest fish trading transactions in Banda Aceh. Determination of the price of fish dominated by Toke Bangku, the price has been going for a long time. It is indicated that the sale and purchase are not based on willingness and is fair, while the toke bangku for the bench sets the selling price of fish depending on the weather and market conditions. This study employed a descriptive analysis method, and the data were analyzed qualitatively. The data were collected based on field research and literature review. The results showed that the price set by toke bangku was not according to fisherman because of the law of the price, while toke bangku determination of the selling price was following the weather conditions at sea and market. In the review of Acehnese custom, the price-fixing of toke bangku accordance with law and custom since of the Aceh Sultanate. Whereas according to the perspective of Islamic economics, toke bangku and fisherman get the reward in world and hereafter. It indicates that the value of monotheism is always embedded in life.